Penerapan model pembelajaran multiple intelligences untuk meningkatkan kreativitas berpendapat peserta didik dalam pembelajaran bahasa indonesia kelas 1 di sekolah dasar - Ayu Fitria; Siti Istiyati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2024)
This research aims to increase creativity in opinion through the application of the multiple intelligences learning model in class I students at SD Negeri Duwet 01 Sukoharjo Regency for the 2023/2024 academic year. by applying the multiple intelligences learning model. This research is Classroom Action Research (PTK) which was carried out in two cycles in one cycle consisting of two meetings. Each cycle consists of four stages, namely planning, action, observation and reflection. The research subjects were teachers and students of class 1 at SD Negeri Duwet 01 Sukoharjo Regency with a total of 20 students. The data used is qualitative and quantitative data. Data collection techniques use non-test techniques in the form of observation, interviews, and documentation as well as test techniques. The data validity testing techniques used are source triangulation and technique triangulation. The data analysis technique used in this research uses the Miles and Huberman analysis model which consists of data reduction, data presentation, and drawing conclusions. The results of this research show that the creativity of students' opinions increases in each cycle. Before the implementation of creativity completion measures, students only had 15% opinion. Cycle I increased to 45% and in cycle II it reached 90%. The conclusion of this research is that the application of the multiple intelligences learning model is able to increase the creativity of opinion of grade 1 students at SD Negeri Duwet 01.Kata kunci: application of learning models, multiple intelligences, creativity of opinion, Indonesian, elementary school